2022
DOI: 10.23887/ivcej.v5i1.44227
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of Social Skills Training On The Ability To Cooperate In Early Childhood

Abstract: The problem is that children's cooperative abilities are still low because teachers tend to give individual assignments and rarely give group assignments that allow children to work with their friends. This study analyzes social skill training on the ability to cooperate in group B Kindergarten children. This research is quasi-experimental research using a non-equivalent pretest-posttest control group design. The research population was 69 students—the sample with cluster random sampling technique. The sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
2
0
3
Order By: Relevance
“…Social skills allow students to communicate what they have learned and what they have not understood. Students will also easily work on assignments in groups with good collaboration (Bali, 2017;Fikri, 2022). In accordance with the purpose of the study conducted, that social skills are improved in teaching social studies, by making the values of Umma kalada a source of learning, learning that increases local wisdom can improve positive communication between students improve what they feel part of same culture (Siregar et al, 2019;Suryanti et al, 2020).…”
Section: Discussionmentioning
confidence: 85%
“…Social skills allow students to communicate what they have learned and what they have not understood. Students will also easily work on assignments in groups with good collaboration (Bali, 2017;Fikri, 2022). In accordance with the purpose of the study conducted, that social skills are improved in teaching social studies, by making the values of Umma kalada a source of learning, learning that increases local wisdom can improve positive communication between students improve what they feel part of same culture (Siregar et al, 2019;Suryanti et al, 2020).…”
Section: Discussionmentioning
confidence: 85%
“…The highest level was reported for interaction and participation skills, whereas the emotional skills were reported to be at the lowest level. The social skills training had a positive effect on the cooperative skills of the children at the early childhood education level (Fikri & Tegeh, 2022). An experimental study conducted during COVID-19 also reported a positive change in the social skills of the children (Nurjanah, Machmudah, Zahroh, Ainiyah, Hasina & Kamariyah, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Dengan keterampilan sosial, manusia mampu memperoleh keharmonisan untuk beradaptasi di masyarakat atau bahkan di sekolah. Dengan demikian, keterampilan sosial adalah kemampuan manusia untuk hidup, dan seluruh kegiatan diterima dengan baik di lingkungan sosial (Febrian Al Amin, 2019;Fikri & Tegeh, 2022). Keterampilan sosial juga disebut dengan keterampilan hidup manusia untuk membuat semua kegiatan dapat diterima di lingkungan masyarakat (Hardhiyanti et al, 2020;Meitya et al, 2017).…”
Section: Pendahuluanunclassified
“…Dengan adanya keterampilan sosial yang dimiliki oleh siswa, dapat mempengaruhi keberhasilan hubungan sosial dan mendorong individu untuk berkolaborasi dengan orang lain secara efektif. Oleh karenanya, keterampilan sosial harus dimiliki pada anak sejak usia dini agar dapat berinteraksi secara baik dengan orang lain, sehingga individu tersebut dapat diterima oleh masyarakat di kemudian hari (Febrian Al Amin, 2019;Fikri & Tegeh, 2022;Hardhiyanti et al, 2020;Meitya et al, 2017).…”
Section: Metodeunclassified